Pengaruh Pendekatan Saintifik Pada Mata Pelajaran Fikih Terhadap Minat Belajar Siswa Kelas V MI Muhammadiyah Tegalurung - Muzfirah, Suci; Afdal, Muhammad; Mubarok, Frenky (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Lack of student interest in fiqh lessons is one of the problems that occur in educational institutions. Fiqh learning in the Madrasah Ibtidaiyah curriculum is one of the subjects that is directed to prepare students for the ability to recognize, understand, appreciate, and practice Islamic law, which then becomes the basis for a way of life through guidance, teaching, training, and experience activities. This study aims to determine the effect of the scientific approach to fiqh subjects on the learning interests of class V students of MI Muhammadiyah Tegalurung. This type of research uses quantitative descriptive. To obtain the data studied, the researcher took data from the sample in this study using 1 class, namely class V A as the experimental class, the data collection method in this study used a questionnaire, while for the data analysis technique in this study using the R Square test Based on the SPSS output table "Model Summary" above, it is known that the determination coefficient value or R Square is 0.757. The R Square value of 0.757 comes from the squaring of the correlation coefficient value or "R", which is 0.870 x 0.870 = 0.757. The magnitude of the determination coefficient (R Square) is 0.757 or equal to 75.7%. This figure means that the motivation variable (X1) and the interest variable (X2) simultaneously (together) affect the achievement variable (Y) by 75.7%. While the rest (100% - 75.7% = 24.3%) is influenced by other variables outside this regression equation or variables that are not studied. Based on the results of the study above, it shows that there is a positive influence between the influence of the scientific approach on students' learning interests at MI Muhammadiyah Tegalurung, from here it can be concluded that the hypothesis can be accepted and proven. It is hoped that this thesis will be a source of information and input for those who read it and can be used as a reference for further research.